Appointment Planning in Outpatient Clinics and Diagnostic Facilities - Zonderland, Maartje E.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2014)
Appointment Planning in Outpatient Clinics and Diagnostic Facilities provides a concise overview of the medical and mathematical aspects of appointment planning in healthcare. This SpringerBrief specifically focuses on outpatient clinics and diagnostic facilities. It begins by introducing the topic from a medical perspective, discussing the kinds of clinics and facilities that are out there, while exploring the appointment systems they use and the problems they face. Next, the mathematical aspects of appointment planning are examined, including Markov decision modelling, queueing theory, etc. Subsequently the book addresses implementation issues that may arise, whether they be technical, medical or cultural. Finally Appointment Planning in Outpatient Clinics and Diagnostic Facilities provides an outlook on the appointment systems of the future and what they will require as a consequence of current and future developments in the medical sector.
Introduction -- Mathematical Models for Appointment Planning -- Basic Queuing Theory -- Access Time and Waiting List Management -- Scheduling Appointment Slots -- Specific Appointment systems -- Improving Clinic Operations -- Challenges in Appointment Planning.
Keywords: Economics; Operations research; Economics/Management Science; Health Care Management; Operation Research/Decision Theory; Practice Management